Highly modified and immunoactive N-glycans of the canine heartworm - Francesca Martini (Nature Portfolio, 2019)
The glycome of parasites can have immunomodulatory properties or help to avoid immune surveillance, but details are unknown. Here, Martini et al. characterize the N-glycome of the canine heartworm, reveal an unprecedented complexity, particularly in anionic N-glycans, and determine recognition by components of the immune system.